2016
DOI: 10.7251/comen1602091o
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protective Varnishes in the Treatment of Initial Caries

Abstract: Objective: The aim of this study was to examine the impact of fluoride varnish and a new generation of nanoapatite varnish containing both Casein PhosphoPeptide − Amorphous Calcium Phosphate (CPP-ACP) and fluoride, on the activity of the initial smooth surface caries lesions of primary teeth. Materials and Methods: A randomized clinical trial was conducted on a total of 120 primary teeth with initial caries lesions in enamel, at children under the age of 24 months. Clinical evaluation of initial carious lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…16 To date, majority of published studies demonstrated superiority of CPP-ACP fluoride varnishes when compared to conventional fluoride varnishes. [17][18][19][20] However, in our study the comparison of remineralisation efficacy between the G1 and CPP-ACP compounds fluoride varnish was not significant. it was concluded that both fluoride…”
Section: Discussioncontrasting
confidence: 77%
“…16 To date, majority of published studies demonstrated superiority of CPP-ACP fluoride varnishes when compared to conventional fluoride varnishes. [17][18][19][20] However, in our study the comparison of remineralisation efficacy between the G1 and CPP-ACP compounds fluoride varnish was not significant. it was concluded that both fluoride…”
Section: Discussioncontrasting
confidence: 77%
“…However, CPP-ACPF varnish did not possess better remineralization potential than Duraphat varnish ( Mohd Said et al, 2017 , Üstün and Aktören, 2019 ). In a clinical investigation conducted by Obradovi et al, CPP ACPF varnish demonstrated superior remineralization versus standard varnish for early smooth surface caries lesions of primary teeth ( Obradović et al, 2016 ). CPP-ACP varnish appears to be equally effective as other fluoride varnishes in remineralizing artificially generated white spot lesions, although the quality of the evidence is low, according to a meta -analysis study ( Nadar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 38 ] In a clinical trial by Obradović et al ., CPP-ACPF varnish showed better remineralization of initial smooth surface caries lesions of primary teeth compared to conventional varnish with fluoride. [ 50 ] A systematic review and meta-analysis on randomized controlled trials by Tao et al . concluded that fluorides combined with CPP-ACP treatment produce significantly better remineralization of occlusal early caries lesions.…”
Section: Discussionmentioning
confidence: 99%